Dapatkah Investasi Teknologi Informasi Memoderasi Keberagaman Gender Dewan dan Konservatisme Akuntansi? - Irvan Nurdin Aziz; Indira Januarti (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to examine the influence of board gender diversity on accounting conservatism and technology information investment as moderating variables. Methodology/approach: This research is a quantitative study. The population in this research is the banking sector industry for the period 2020-2022. Purposive sampling technique was applied, resulting in a final sample of 40 companies or 120 observation data. The data was sourced from annual reports accessible through the official website of the Indonesia Stock Exchange (BEI). The data were analyzed through moderation effect tests by Eviews 9.0. Findings: The gender diversity on the board of directors and investment in information technology have a positive impact on accounting conservatism. Additionally, investment in information technology can moderate the relationship between gender diversity on the board and accounting conservatism by altering the direction of their relationship. Practical and Theoretical contribution/ Originality: Theoretically, the research findings contribute to accounting literature. Practically, it suggests that banking companies pay attention to gender composition when designing accounting policies and technology investment strategies. Research Limitation: This study discusses diversity solely in terms of gender, yet there are many other dimensions of diversity that future research could explore, such as ethnicity, age, educational background, and professional expertise.